2019
DOI: 10.1136/bmjopen-2019-032218
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of vaccine hesitancy in Switzerland: study protocol of a mixed-methods national research programme

Abstract: IntroductionVaccine hesitancy is a complex public health issue referring to concerns about the safety, efficacy or need for vaccination. Relatively little is known about vaccine hesitancy in Switzerland. This ongoing study (2017–2021) focuses on biomedical and complementary and alternative medicine (CAM) providers and their patients since healthcare professionals play important roles in vaccination decision-making. This national research programme seeks to assess the sociocultural determinants of vaccine hesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 62 publications
0
57
0
Order By: Relevance
“…Switzerland values plurality and policy diversity among its different cantons; this is reflected in the cantons' different immunization programs and outcomes. Deficiencies in vaccine compliance among cantons have been attributed to differing priorities and practices of policy makers and attitudes of vaccine gate-keepers (e.g., nurses, general practitioners) and engagement in alternative health care and education pedagogies [32,53,62]. Swiss communities report an openness to public programs if their autonomous decision-making is respected [62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Switzerland values plurality and policy diversity among its different cantons; this is reflected in the cantons' different immunization programs and outcomes. Deficiencies in vaccine compliance among cantons have been attributed to differing priorities and practices of policy makers and attitudes of vaccine gate-keepers (e.g., nurses, general practitioners) and engagement in alternative health care and education pedagogies [32,53,62]. Swiss communities report an openness to public programs if their autonomous decision-making is respected [62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the fact that the determinants of vaccine hesitancy and compliance are not fully understood and hence require further study, 34 researchers found that there is no universally accepted reality regarding the issue and recommended context-specific research. 6 The objective of the present study was, therefore, to examine willingness to take a Covid-19 vaccine among people working in occupations that put employees relatively at a higher risk of infection with Covid-19 in Wolaita Sodo town, Southern Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show a complex association between complementary and alternative medicine (CAM) use and VH [11], with popular narratives typically decrying CAM users and providers as categorically anti-vaccine [12]. However, research conducted in the setting of our national research program on VH [13,14] has suggested that providers of CAM in Switzerland are not categorically anti-vaccine. They prefer providing individualized vaccination counseling, which includes taking time to understand parent vaccine wishes, involving parents in vaccine decisions, and taking their vaccine concerns seriously [15].…”
Section: Introductionmentioning
confidence: 99%
“…Be aware of one of the major determinants of vaccine hesitancy: the prevalent perception that the health authorities are collaborating with and/or influenced by vaccine manufacturers On a larger scale, our ongoing National Research Program on vaccine hesitancy [13,14] has recruited a network of more than 150 medical professionals throughout Switzerland, including more than 40 CAM practitioners. Given the popularity and interest towards CAM of the Swiss population [21,22] and from pediatricians [26], the incorporation of CAM perspectives and engagement with practitioners of both CAM and biomedicine into vaccination communication strategies is, in our view, a feasible, innovative, and reasonable approach to addressing VH in the Swiss context.…”
mentioning
confidence: 99%